How to Approach Acid Base Disorders: Reprinted for our readers interest originally published PJKD 2018;2(4):38-42. - Professor Dr. Tahir Shafi (Pakistan Journal of Kidney Diseases, 2021)
The pH in the body is maintained within a narrow range for the adequate metabolic functions and enzymatic processes. Timely and accurate diagnosis of acid base disorder can be life saving. For proper diagnosis and treatment of acid base disorders you need clinical data, laboratory data, correlation of clinical and laboratory data to see if the laboratory diagnosis fits in clinical scenario and then treatment of acid base disorder and the underlying disease.